What makes a good job? Job quality and job satisfaction - Andrew E. Clark (IZA World of Labor, 2015)
Many measures of job satisfaction have been trending downward. Because jobs are a key part of most people's lives, knowing what makes a good job (job quality) is vital to knowing how well society is doing. Integral to worker well-being, job quality also affects the labor market through related decisions on whether to work, whether to quit, and how much effort to put into a job. Empirical work on what constitutes a good job finds that workers value more than wages; they also value job security and interest in their work. Policy to affect job quality requires information on the cost of the different aspects of job quality and how much workers value them.
Keywords: J28; J3; J81; 330; job quality; job satisfaction; welfare; mismatch